Impact of childhood maltreatment on obsessive-compulsive disorder symptom severity and treatment outcome - Sabrina Boger (European Journal of Psychotraumatology, 2020)
Background Preliminary evidence suggests childhood maltreatment to play a causal role in the development and maintenance of obsessive-compulsive disorder (OCD). However, both the effect of childhood maltreatment on the course of OCD treatment and the role of specific subtypes of maltreatment remain largely unknown. Objective This study aimed to investigate the relationship between childhood maltreatment and the severity and time course of OCD symptoms within a clinical sample of OCD patients (N = 68). We hypothesized that higher levels of childhood maltreatment in OCD patients would be associated with higher symptom severity and worse treatment outcomes. Method Assessments of childhood maltreatment, OCD symptomatology, and related variables were completed in a sample of OCD patients before and after inpatient treatment as well as at 6 month follow-up. Results Emotional abuse, sexual abuse and neglect were highly prevalent in our sample. Additionally, the severity of experienced childhood maltreatment was associated with higher OCD symptom severity, with the strongest association found for emotional abuse. Hierarchical linear models indicated that patients with childhood maltreatment showed higher OCD symptom severity at pre-treatment, post-treatment, and follow-up compared to patients without these experiences. However, childhood maltreatment did not moderate symptom improvement during treatment. Conclusion Thus, although childhood maltreatment is not related to treatment outcome, it is highly prevalent among OCD patients and childhood trauma survivors still show higher OCD symptom severity after treatment. Therefore, childhood maltreatment should be considered in psychological interventions in individuals with OCD.